Felicidade no trabalho e interação familiar em enfermeiros: estudo transversal - Loureiro, Sofia Alexandra Ribeiro; Loureiro, Helena Maria Almeida Macedo; Trindade, Letícia de Lima; Borges, Elisabete Maria Neves (Revista de Enfermagem da UFSM, 2023)
Objective: to analyze the association among happiness at work, family interaction and sociodemographic/professional variables in nurses in the hospital context. Methods: cross-sectional study with a convenience sample of 363 nurses. Questionnaires for sociodemographic/professional characterization, Shorted Happiness at Work Scale and Survey Work-Home Interaction Nijmegen were applied. In data analysis and processing, descriptive and inferential statistics were used. Results: moderate levels of happiness at work (4.44±1.15) and moderate to low levels of family interaction (1.02±0.31) were observed. Marital status, leisure activities, place of work, length of professional experience, professional category, working hours and perception of stressful work were associated with happiness at work. Age, gender, children, dependents, leisure activities, length of professional experience, working hours and perception of stressful work were associated with family interaction. Conclusion: nurses showed moderate levels of happiness at work and moderate to low levels of family interaction, associated with specific sociodemographic and professional variables.